Fungsi, Kategori, dan Peran Sintaksis Bahasa Indonesia dalam Kalimat Efektif Teks Cerita Anak yang Berjudul “Berbeda Itu Tak Apa” pada Buku Ajar Bahasa Indonesia Kelas Satu Sekolah Dasar Kurikulum Merdeka - Nurul Lisa Kusumaningrum; Erina Hidayah; Vivin Widya Sari; Salma Dian Rhamadhan; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Student Research Journal, 2023)
Children's story text is an event based on the time sequence experienced or in the form of imagination that tells the world of children. This story text can improve the process of language skills in children by reading. The children's story text entitled "Different It's Okay" has an interesting story to be studied, namely effective sentences that will be analyzed using syntactic functions, roles, and categories. This research aims to classify words in the Indonesian language textbook for grade one of the independent curriculum elementary school. This research analysis uses a qualitative descriptive method. The techniques used to collect data in this research are reading and note-taking techniques, or listening. The results of this study can be found in the role, function, and syntactic category in the Indonesian language textbook for grade one of the independent curriculum elementary school. This research is useful for helping students in the process of analyzing syntactic structures.